Effects of micronutrients and macronutrients on risk of allergic disease in the European population: a Mendelian randomization study - Xiangyue Zeng; Zhimin Wu; Yipeng Pan; Yifei Ma; Yi Chen; Zeliang Zhao (Food and Agricultural Immunology)
Background: Regional lifestyles influence allergic disease risks, with dietary factors being crucial. However, observational studies on micro- and macronutrient impacts are inconsistent.Methods: We used a two-sample Mendelian randomization (MR) design with the inverse variance weighted (IVW) method and sensitivity analyses to evaluate the effects of various micronutrients (e.g. zinc, selenium, phosphorus) and macronutrient intake on allergic diseases.Results: Zinc was inversely associated with allergic asthma (OR = 0.856, p = 0.014) and atopic dermatitis (OR = 0.918, p = 0.039). Selenium was inversely associated with allergic rhinitis (OR = 0.863, p = 0.037). Phosphorus was linked to an increased risk of allergic urticaria (OR = 4.396, p = 0.0025). Other nutrients showed no significant associations.Conclusion: Certain micronutrients, like zinc, selenium, and phosphorus, may play significant roles in allergic disease development, warranting further research to confirm these findings.